A contemporary team process management model to enhance multicultural and multidisciplinary virtual team performance. (2015) - Siakas, Kerstin; Siakas, Errikos
This paper aims to reveal experiences gained from multicultural and multidisciplinary virtual collaborative teamwork within projects sponsored by the EU. The members of the consortium, often unknown to each other, comprise a variety of experts of diverse cultural, organisational, and professional backgrounds. Within the project lifetime they are connected together with time and money constraints for a specific period of time to accomplish certain distinctive objectives. A conceptual team process management (TPM) model was developed to support teams and increase performance. The ultimate outcome the TPM model helped in overcoming apparent complexities and contradictions due to the structure the model provides.